On warfare and the threefold path of the Jerusalem pilgrimage : a translation of Ralph Niger's De Re Militari et Triplici via peregrinationis Ierosolimitane - Radulfus, Niger, approximately 1140-; Cotts, John D. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This volume will provide the first English translation of Ralph Niger's critical reflection on military pilgrimage, written in the late 1180s in response to the calling of the Third Crusade. Long known to scholars as early and highly idiosyncratic critique of crusading, On Warfare and the Threefold Path of the Jerusalem Pilgrimage provides a sustained reflection on penance, the meaning of Jerusalem, and the challenges of military expeditions to the Levant. After the fall of Jerusalem, he resisted the calls to crusade and instead exhorted on Christians to look inward and build Jerusalem in their hearts. Throughout the four books of the work, Ralph looks to scripture for precedents for crusading and finds none. However, by ranging widely over examples of Old Testament violence and considering the Heavenly and Earthly Jerusalem together. On Warfare offers a unique perspective on how the Bible informed contemporary views of the Crusades. Methodically examining pilgrimage through the lens of scripture, Ralph surveys the entire semantic field of crusading, and concludes that Christian knights could do more good by staying home than going on a military adventure to the Holy Land"--
Keywords: Bible -- Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.; Crusades -- Third, 1189-1192.; Pilgrims and pilgrimages; HISTORY / General